Numerical Evaluation of Foundation of Digester Tank of Sewage Treatment Plant - Mahdi O Karkush; Ala N. Aljorany (Salehan Institute of Higher Education, 2019)
In the present study the foundation of digester tank, main part of sewage treatment plant, is reanalyzed analytically and numerically to check the adequacy of such foundation to support superstructure loading. The foundation of digester tank consists of raft foundation and bored piles. The diameter of raft is 33 m and thickness of 1 m, while the piles are bored type of diameter 0.6 m and length 15 m. After testing eleven working piles, it is found that three piles cannot support a load of 1.5 times the working load (1305 kN) safely or in other words the factor of safety of these failed piles is less than 1.5. The results of filed pile tests are reanalyzed using two well-known methods, Davisson’s method and Brinch-Hansen method to check the ultimate carrying capacity of tested piles. Also, this paper includes analysis of previous soil investigation report and conducting additional soil investigation by drilling three boreholes to secure the soil parameters used in the analytical and numerical analysis of digester tank foundation. SAFE 12 software is used to analysis the foundation of structure as piled-raft instead of pile group to interest from the interaction between soil and raft foundation. The results of analysis showed that the piles failed in the tests can support its share of the superstructure load by a factor of safety 1.8 and the piles success in the field tests can support its share of the superstructure load by a factor of safety not less than 2.86. Also, the settlement under structure will be less than 100 mm, where using piled-raft analysis reduces the settlement to be within allowable limits.